NYPD Red 6 - Patterson, James, 1947-; Karp, Marshall; Snyder, Jay, 1971- (New York, NY : Hachette Audio, 2020)
Reality star Erin Eastons wedding may have a cable crew documenting every detail. But when she disappears, her dressing room is empty but for a blood-spattered wedding gown and signs of a struggle.
Keywords: MacDonald, Kylie -- (Fictitious character) -- Fiction; Jordan, Zach -- (Fictitious character) -- Fiction; Police -- New York (State); New York; Fiction; Kidnapping -- Investigation; Fiction; Women -- Crimes against; Fiction; Actresses -- Fiction; Weddings -- Fiction; Reality television programs -- Fiction; Motion pictures -- Production and direction -- New York (State); New York; Fiction; Internet videos -- Fiction; New York (N.Y.) -- Fiction; Suspense fiction; Thrillers (Fiction); Audiobooks